Three new species of Tricholomopsis (incertae sedis) from North China based on morphological and molecular data - Mao, Ning; Xu, Yu-Yan; Fan, Li (Phytotaxa, 2021)
Three new species of Tricholomopsis were described and illustrated based on collections from Shanxi Province in North China. Tricholomopsis galeata sp. nov. is closely related to T. pteridiicola but distinguished from the latter by its large pileus with red to purple reddish fibrous scales and the absence of pleurocystidia. Tricholomopsis pallidolutea sp. nov. is similar to T. sulfureoides and T. flavescens in macromorphology but is differentiated from T. sulfureoides by its dark orange fibrous scales on the pileal surface and narrow basidiospores (avQ = 1.77 ± 0.33), and from T. flavescens by its abundant pleurocystidia. Tricholomopsis mitirubicunda sp. nov. is morphologically similar to T. rutilans but is distinguished from the latter by its abundant pleurocystidia. Phylogenetic analysis supported the taxonomic position of the three new species in the genus Tricholomopsis.